Comparative Study of Paradigm on Character Education Perspective by Paulo Freire and Ki Hajar Dewantara - Putri, Shafira Arifah (Proceeding International Conference on Science and Engineering, 2020)
Nowadays, when science and technology continue to grow rapidly, character education precisely more gets eroded. It shows, there has been morals degradation in the middle global mainstreaming. The authors using of character education prespective by two phenomenal figures to be discussed, Paulo Freire and Ki Hajar Dewantara. Both give a more attention to the paradigm education that is able to answer new challenges. Freire thought to give a solution by is leaving magical and naive education, switch to concept critical education that freed humans leads to a new colour in the proggressive change. Whereas, thought Dewantara to show a concept “trilogi” that is how the role family, school, and public able to formation movers character and children mentality along through system “among” based on Ing Ngarsa Sang Tuladha, Ing Madya Karsa, and Tut Wuri Handayani. The method that is used in this research analytic comparative method, that is by to analyze in a looking for sides similarity and difference of thought. The purpose of this research is to describe character students towards the future better.